Inumanos demasiado humanos : normas, fantasmas e máquinas em A desumanização e em A máquina de fazer espanhóis, de Valter Hugo Mãe - Guimarães, Thiago Maciel (2022)
In this study, we undertake an analysis of the functioning of despotic norms that appear within two novels by the portuguese writer Valter Hugo Mãe: a máquina de fazer espanhóis (2010) and A desumanização (2013). Based on the principles of the phenomenological-hermeneutic method, we seek a combination of history, literary theory and philosophy. The way of theoretical understanding of the meaning of Art, according to the elaborations of Georg Lukács (1965) and Friedrich Nietzsche (1880), was also a theoretical-methodological effort that permeated the entire examination. We begin by explaining, within the scope of the research, the abnormal value potentially represented by literature in human society and mirrored in the novel genre and in the persistent transits between prose, poem and poetry that intertwine in it. Then, we approach the way that death drives the main characters to build their narratives. Together, we ponder how the dynamics of silence and silencing (ORLANDI, 2007; SONTAG, 1967; FOUCAULT, 1970) are able to paradoxically display the imbalances and despotisms in the societies portrayed in the works. Our efforts were guided by the historical location made by Michel Foucault (1975) regarding the construction of the abnormal and human abnormality through legal and psychiatric discourses, mainly from the 19th century; we also relate how these meanings, very prevalent in contemporary times, are present in both novels and affect the characters' perception of themselves and others. We continue the journey by examining the relationships between the Same and the Other (FOUCAULT, 1966) and the consequences presented in the social order in the stories from the narrators' report. The path culminates in the timelessness of questioning ghosts, resorting to the elaborations of Jacques Derrida (1994). Then, we look at the functioning of despotic machines that broker the desires of other machines, according to the meaning of Gilles Deleuze and Félix Guattari (1975), to show the contribution of Valter Hugo Mãe to the set of machines critical to the Salazar period, in addition to to invest in the understanding of the perenniality of the modes of functioning of fascism still present in many contexts in the social relations updated in the novels.